Enzymes for Pancreatic Islet Isolation Impact Chemokine-Production and Polarization of Insulin-Producing β-Cells with Reduced Functional Survival of Immunoisolated Rat Islet-Allografts as a Consequence - de Vos, Paul (PLoS One, 2016)
The primary aim of this study was to determine whether normal variations in enzyme-activities of collagenases applied for rat-islet isolation impact longevity of encapsulated islet grafts. Also we studied the functional and immunological properties of rat islets isolated with different enzyme preparations to determine whether this impacts these parameters. Rat-islets were isolated from the pancreas with two different collagenases with commonly accepted collagenase, neutral protease, and clostripain activities. Islets had a similar and acceptable glucose-induced insulin-release profile but a profound statistical significant difference in production of the chemokines IP-10 and Gro-α. The islets were studied with nanotomy which is an EM-based technology for unbiased study of ultrastructural features of islets such as cell-cell contacts, endocrine-cell condition, ER stress, mitochondrial conditions, and cell polarization. The islet-batch with higher chemokine-production had a lower amount of polarized insulin-producing β-cells. All islets had more intercellular spaces and less interconnected areas with tight cell-cell junctions when compared to islets in the pancreas. Islet-graft function was studied by implanting encapsulated and free islet grafts in rat recipients. Alginate-based encapsulated grafts isolated with the enzyme-lot inducing higher chemokine production and lower polarization survived for a two-fold shorter period of time. The lower survival-time of the encapsulated grafts was correlated with a higher influx of inflammatory cells at 7 days after implantation. Islets from the same two batches transplanted as free unencapsulated-graft, did not show any difference in survival or function in vivo. Lack of insight in factors contributing to the current lab-to-lab variation in longevity of encapsulated islet-grafts is considered to be a threat for clinical application. Our data suggest that seemingly minor variations in activity of enzymes applied for islet-isolation might contribute to longevity-variations of immunoisolated islet-grafts.